Using digraphs to compute determinant, permanent, and Drazin inverse of circulant matrices with two parameters - Encinas Bachiller, Andrés Marcos (2024)
This work presents closed formulas for determinant, permanent, inverse, and Drazin inverse of circulant matrices with two non-zero coefficients.